C-Reactive Protein/Albumin Ratio as Predictor of COVID-19 Severity and Mortality - Ali Hashim Ibrahim, Jehan; Emad Abbas, Zahraa (South Asian Journal of Social Sciences and Humanities, 2025)
Background: Early detection of COVID-19 patients with a higher risk of infection advancement can help tailor treatment plans more specifically and ensure better allocation of  healthcare resources. Both C-reactive protein also albumin serve as markers that are sensitive  to inflammation. Study objective: evaluate the ability of CRP/ and Alb proportion in the  prediction of cruelty and mortality of COVID-19 infection. Method: sample of 130 clients  with COVID that confirmed outcomes entered the private nursing home \ medical city,  Baghdad, Iraq, between January - October 2023. Patients are divided into mild, moderate and  severe, and into dead and alive patients. To predict disease progression, CRP, albumin and  CRP\Alb ratio were evaluated on admission. Results: A study of 130 patients with COVID-19 infection, mean age of (53.80 ± 16.33) years old, (48.5%) of patients are females, while (51.5%)  of patients are males. (66.92%) of patients have severe infection, while (33.08%) of them have  non-severe (mild and moderate) infection with COVID-19. High CRP\Alb ratio occurs more  in severe COVID infection and those who died than in non-severe (mild and moderate) and  those who were discharged alive, respectively. Conclusion: CRP/and albumin percentage may  serve consider early indicator of the development of severe illness or death, offering a  predictive biomarker to assess risk and guiding the clinical interventions of COVID-19 clients.
Keywords: CRP\Alb ratio; COVID-19; severity; mortality.